Performance Evaluation of Cooked Mid-Day Meal (CMDM) - Planning Commission (Planning Commission Government of India, 2010)
The Cooked Mid-Day Meal (CMDM) scheme, launched in 1995 under India’s National Programme for Nutrition Support to Primary Education, aims to improve child nutrition while enhancing school attendance and retention. The 2010 evaluation across 17 states revealed nearly universal coverage, with positive impacts on attendance and social inclusion. However, significant challenges persist, including inadequate kitchen infrastructure, shortage of trained cooks, low honoraria, insufficient meal quality and variety, and poor record-keeping practices. While CMDM had limited influence on new student enrollment, it contributed to reducing classroom hunger and promoting equitable access for socially disadvantaged groups. The study recommends increasing cook honoraria, improving infrastructure and meal quality, standardizing record maintenance, enhancing community participation, and linking CMDM more closely with broader educational initiatives to maximize its impact on child nutrition and learning outcomes.
Programme Evaluation Organisation Planning Commission Government of India New Delhi-110001 May 2010
Keywords: Cooked Mid-Day Meal; Nutritional Support; School Attendance; Enrollment; Infrastructure; Staffing; Meal Quality; Social Equity; Community Participation; Record Keeping; Student Satisfaction; Educational Outcomes